E-LEARNING ADOPTION FACTORS AMONG FSJES STUDENTS IN FEZ, MOROCCO: A SURVEY INSPIRED BY UTAUT: Received: 8th April 2024 Revised: 30th April 2024, 11th May 2024, 24th July 2024 Accepted: 15th April 2024 - Ouzif, Hicham; El Boukhari, Hayat (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This article discusses the results of a research study conducted in the field, examining the factors influencing the uptake of E-learning platforms among students at the Faculty of Legal, Economic, and Social Sciences (FSJES) in Fez, Morocco. The study utilizes the Unified Theory of Acceptance and Use of Technology (UTAUT) as its theoretical foundation. The methodology employed in this study utilized a quantitative approach to collect measurable and objective data regarding the factors influencing the adoption of E-learning. A sample of 144 students participated, responding to electronic questionnaires designed to assess key dimensions of the UTAUT model, such as expected performance, perceived effort, social influence, and ease of use. Interpreted through the lens of UTAUT, the results provide significant insights into the factors influencing E-learning adoption among FSJES Fez students. These findings enhance the understanding of determinants specific to this student population and institution, offering avenues for targeted interventions to promote successful E-learning adoption.